Пеймыт уй гинэ вералоз: документьёсъя гожтэм повесть но очеркъёс / Н. Н. Евсеев - Евсеев Николай Николаевич (Удмуртия, 1995)
Экземпляры: (20240111) / Инвентарный номер: 25388 / Цена: 1.80 / Сис.шифр: 63.3(2Рос-6Удм) / Авт.знак: Е 25 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)